Long-term phosphorus immobilization by a drinking water treatment residual - Agyin-Birikorang, Sampson; O'Connor, George A.; Jacobs, Lee W.; Brinton, Scott R.; Makris, Konstantinos C. (My University, 2007)
Excessive soluble P in runoff is a common cause of eutrophication in fresh waters. Evidence indicates that drinking water treatment residuals (WTRs) can reduce soluble P concentrations in P-impacted soils in the short term (days to weeks). The long-term (years) stability of WTR-immobilized P has been inferred, but validating field data are scarce. This research was undertaken at two Michigan field sites with a history of heavy manure applications to study the longevity of alum-based WTR (Al-WTR) effects on P solubility over time (7.5 yr). At both sites, amendment with Al-WTR reduced water-soluble P (WSP) concentration by ≥60% as compared to the control plots, and the Al-WTR-immobilized P (WTR-P) remained stable 7.5 yr after Al-WTR application. Rainfall simulation techniques were utilized to investigate P losses in runoff and leachate from surface soils of the field sites at 7.5 yr after Al-WTR application. At both sites, amendment with Al-WTR reduced dissolved P and bioavailable P (BAP) by >50% as compared to the control plots, showing that WTR-immobilized P remained nonlabile even 7.5 yr after Al-WTR amendment. Thus, WTR-immobilized P would not be expected to dissolve into runoff and leachate to contaminate surface waters or ground water. Even if WTR-P is lost via erosion to surface waters, the bioavailability of the immobilized P should be minimal and should have negligible effects on water quality. However, if the WTR particles are destroyed by extreme conditions, P loss to water could pose a eutrophication risk.
Keywords: Computer simulation; Eutrophication; Leachate treatment; Phosphorus; Rain; Runoff; Soils; Water treatment; Phosphorus immobilization; Rainfall simulation techniques; Water treatment residuals (WTR)